Cytogenetic Remissions Induced by Interferon α and Imatinib Mesylate are Immunologically Distinct in Chronic Myeloid Leukemia - Nakayama, Shin; Nagamura-Inoue, Tokiko; Yokoyama, Kazuaki; Ohno, Nobuhiro; Ooi, Jun; Takahashi, Satoshi; Uchimaru, Kaoru; Iseki, Toru; Tojo, Arinobu (International journal of hematology, 2007)
We compared immunologic parameters of chronic myeloid leukemia (CML) patients in cytogenetic remission receiving imatinib mesylate (STI) treatment, CML patients receiving interferon alpha (IFN-alpha), and healthy volunteers. Each group comprised 14 subjects. Median treatment dosages and durations were 6 x 10(6) IU/week and 174 months, respectively, for IFN-alpha and 400 mg/day and 54 months for STI. The numbers of T-cells were significantly lower in the 2 patient groups (P = .0006), whereas the 3 groups were comparable with respect to the numbers of natural killer cells. Not only the absolute numbers of monocytes and B-cells but also serum immunoglobulin G (IgG) and IgA titers were significantly lower in the STI group than in the IFN-alpha group (P < .0001). For T-cell subsets, the ratio of CD4 T-cells to CD8 T-cells was significantly lower in the IFN-alpha group than in the STI group, but the proportion of CD26(high)CD4+ T-cells among CD4+ cells was significantly higher. Collectively, the 2 therapeutic agents induce a distinct immunologic status in CML patients whose hematopoiesis has returned to normal levels.